MANEJO DE DOENÇAS DA CULTURA DO MILHO: ÓLEOS ESSENCIAIS, FUNGICIDAS E HÍBRIDOS - Trojan, Daiane Garabeli (2016)
The increase in diseases in maize crops, with emphasis on the region of Campos Gerais in Paraná, has been relevant due to the commitment quantitative and qualitative of the grain. Because of this, the purposes of this work were: to evaluate the incidence of leaf diseases and their impact on productivity; to evaluate the effect of different fungicides to control pathogens that cause damaged grains; to relate the incidence of the main leaf diseases in corn crop and its interference with the production components; to evaluate the performance of corn inoculated with Colletotrichum graminicola to treatments with different mixtures of fungicides of strobilurins and triazoles groups; to verify the effect of various essential oils and fungicides on mycelial growth of C. graminicola; to develop a diagrammatic scale to assess the severity of anthracnose leaf blight in maize crop and to verify the best concentration of essential oils in the control of leaf anthracnose and to estimate possible effects of phytotoxicity of the essential oils on the corn crop. For that were installed 14 experimental fields with several hybrids of corn during harvest 2011/12, one in the 2012/13 crop, and one in the 2013/14 crop; in laboratory were installed a 2012 experiment, and another between 2014/15; It was developed a diagrammatic scale in 2015 and carried out an experiment in a greenhouse in 2016. The results brought information such as: between the late material and early ones, the results were specific to each location where Puccinia sorghi, Phaeosphaeria maydis, Exserohilum turcicum had greater severity of disease in 6 of the 9 experiments, and was also the most sensitive in the experiment installed in late materials; there was difference of fungicide control depending on the studied pathogen; regarding to yields higher than 10 tons, the components production that directly interfered were: length and diameter of the ear, number of kernels per row and weight of 1000 grains, on the other hand the most affected yield components in those hybrid with productions around 8.5 tons were: diameter of the ear, number of kernels per row and the 1000 grains; None of the Colletotrichum graminicola application times obtained results regarding the incidence of leaf anthracnose. The treatments with fungicides scored lower percentage of damaged kernels; regarding the use of essential oils, clove, oregano and cinnamon there were inhibitory effect on mycelial growth of C.graminicola at all concentrations tested, citronella, lime and orange, showed fungistatic effects at concentrations of 5 and 10%, while lemongrass and thyme showed better results in concentrations of 15 and 20%; the scale was presented as an assertive tool to quantify the severity of anthracnose leaf blight; it was observed that independent of concentration, all essential oils showed phytotoxicity on corn plants, none of the essential oils in the used concentrations totally controlled C. graminicola.